The Roles of TNF Signaling Pathways in Metabolism of Bone Tumors - Zhou, Haiying; Dong, Yanzhao; Alhaskawi, Ahmad; Lai, Jingtian; Wang, Zewei; Ezzi, Sohaib Hasan Abdullah; Kota, Vishnu Goutham; Abdulla, Mohamed Hasan Abdulla Hasan; Sun, Zhenyu; Lu, Hui (Frontiers in Pharmacology, 2022)
The metabolism of bone tumors is extraordinarily complex and involves many signaling pathways and processes, including the tumor necrosis factor (TNF) signaling pathway, which consists of TNF factors and the TNF receptors that belong to the TNF receptor superfamily (TNFRSF). It is appreciated that signaling events and pathways involving TNFRSF components are essential in coordinating the functions of multiple cell types that act as a host defense network against pathogens and malignant cells, the implications of TNFRSF-related signaling pathways on bone tumor metabolism remains to be summarized, which is one of the significant obstacles to the application of TNF-related treatment modalities in the domain of bone oncology. This review will discuss and summarize the anti-tumor properties of important TNFRSF components concerning benign bone tumors, osteosarcoma, Ewing sarcoma, and metastatic bone tumors.